RATING PERUSAHAAN TERBUKA DI INDONESIA BERDASARKAN ANALISIS DAN PEMBERIAN BOBOT PADA KUALITAS KARAKTERISTIK LAPORAN KEUANGAN - Aprilia, Christina (Universitas Pelita Harapan Medan, 2018)
High-quality information plays an important role and should be obtained by decision makers from a variety of backgrounds. Currently, easy and time saving way frequently used by decision-makers is the use of intermediary analyzes in the form of rating information on the quality of companies financial statements. The purpose of this study is to provide alternative rating of quality measurement information from the Financial Statement Accounting standpoint. Accounting viewpoint question is by using qualitative characteristics as indicators that must be met in a Financial Statement. This study used an exploratory non mainstream approach on 438 companies in Indonesia. The data used was secondary data collected using documentation.The results showed that the rating of companies that have good, and mid quality in qualitative characteristics are in line with the companies rating using other indicators such as compliance with GCG, the resilience of economy, the business continuity assessed using the financial performance, and also the pattern of active shares in the capital market. Hence, it can be concluded that the rating by using qualitative characteristics of financial statements can be used as an alternative way and provide value-added information. This alternative rating way is simpler and easier, but it has benefits for diverse backgrounds decision makers.Â Keywords: Quality of Information, Financial Statements, Qualitative Characteristic, Rating.